(3eMGVQGJ aj GdbGfhf GdJLGQj (B: s (3GdJGLQ,GdGYeGd GdJLGQjI,GdeMd GdJLGQj,GdTQcGJ GdJLGQjI (B/ s - (3YdjGf,eGdcs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3fTCI GdbGfhf GdJLGQj h JWhQg, GdGYeGd GdJLGQjI h CfhGYgG,GdJGLQ h GdJRGeGJg GdbGfhfjI ,GdeMd GdJLGQj,GdTQcGJ GdJLGQjI(B.s
(3eQGLY U(B.98s
Keywords: (3GdbGfhf GdJLGQjs